Reducing infiltration rates of peripheral intravenous cannula: A quality improvement initiative in a neonatal intensive care unit of tertiary care hospital in Northern India - Panghal, Astha; Naranje, Kirti M; Singh, Anita; Pandita, Aakash; Gupta, Girish (Indian Journal of Child Health, 2019)
Background: Peripheral venous access is used for infusion of fluids, medications, and blood products. Penetration of these products through an intravenous (IV) access to surrounding tissues causes infiltration or extravasations injuries. Objective: The objective of the study was to measure the incidence of peripheral IV cannula (PIV) infiltration in neonates and reduce infiltration rate by at least 30 % from baseline rate. Methods: This was a quality improvement (QI) study, conducted in the neonatal intensive care unit from March 2018 to June 2018. All the neonates with PIV cannula irrespective of gestational age, postnatal age, and weight were included in the study. The baseline rate of PIV infiltration was determined. A team of doctors and nurses performed root cause analysis of factors responsible for PIV cannula infiltration using fishbone analysis. Various change ideas were tested through sequential Plan-Do-Study-Act cycles. Results: Infiltration rate of PIV cannula after intervention decreased from a baseline incidence rate of 60.8/100 IV–21.4/100 IV days over the study period. Conclusions: A QI approach was able to accomplish a reduction in the infiltration rates of PIV cannula in our unit.